PREPARING PRESENTATIONS FOR INTERNATIONAL CONFERENCES - Kira B. Prigozhina (Высшее образование в России)
The article considers methods and techniques aimed at developing language skills and competences necessary to successfully deliver scientific presentations at internationalconferences. The author reasons theimportance ofthe course, provides analysis of approaches that could contribute to the effective organization of the course. Special attention is paid to the course topics and material selection, course layout and structuring. The focus is also placed on the structure, features and content of academic presentations for international conferences. Having analysed research work of foreign and Russian scientists on the problem, the author presents content and structure based sample of scientific presentation layout, which conforms to international academic standards.